The ensemble consistency test: from CESM to MPAS and beyond - T. Price-Broncucia; A. Baker; D. Hammerling; M. Duda; R. Morrison (Geoscientific Model Development)
The ensemble consistency test (ECT) and its ultrafast variant (UF-ECT) have become powerful tools in the development community for the identification of unwanted changes in the Community Earth System Model (CESM). By characterizing the distribution of an accepted ensemble of perturbed ultrafast model runs, the UF-ECT is able to identify changes exceeding internal variability in expensive chaotic numerical models with reasonable computational costs. However, up until now this approach has not seen adoption by other communities, in part because the process of adapting the UF-ECT procedure to other models was not clear. In this work we develop a generalized setup framework for applying the UF-ECT to different models and show how our specification of UF-ECT parameters allows us to balance important goals like test sensitivity and computational cost. Finally, we walk through the setup framework in detail and demonstrate the performance of the UF-ECT with our new determined parameters for the Model Across Prediction Scales-Atmosphere (MPAS-A), the substantially updated CESM atmospheric model, and realistic development scenarios.